2021
DOI: 10.1021/acsfoodscitech.0c00034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moderate to High Salinity on the Phytochemical Profiles of Two Salinity-Tolerant Spinach Genotypes

Abstract: Freshwater is a major concern in terms of meeting the growing food demand for the growing population. Recycled waters are currently seen as an alternative, but their higher salinity may impact the yield of most crops and their phytochemical content. In this study, we investigated the effects of five salinity treatments combined with two levels of potassium (K) (deficient K, T1–T5, and enough K, T6–T10) on the phenolic profiles and soluble sugars of two spinach genotypes, Raccoon and Gazelle. We also compared c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Spinach ( Spinacia oleracea ) is a vegetable with a wide array of phytoconstituents such as polyphenols, flavonoids, tocopherols, carotenoids, ascorbates, p -coumarins, vitamins, and polysaccharides, which are responsible for its nutritional properties [ 130 , 131 ]. The prominent antioxidants from spinach identified by different researchers include chlorogenic acid and spinacetins, and their analogs [ 132 ]. However, Mzoughi et al reported the antioxidant activity of polysaccharides from spinach using DPPH, ABTS, and FRAP assays [ 90 ].…”
Section: Antioxidant Activity Of Selected Prominent Foodsmentioning
confidence: 99%
“…Spinach ( Spinacia oleracea ) is a vegetable with a wide array of phytoconstituents such as polyphenols, flavonoids, tocopherols, carotenoids, ascorbates, p -coumarins, vitamins, and polysaccharides, which are responsible for its nutritional properties [ 130 , 131 ]. The prominent antioxidants from spinach identified by different researchers include chlorogenic acid and spinacetins, and their analogs [ 132 ]. However, Mzoughi et al reported the antioxidant activity of polysaccharides from spinach using DPPH, ABTS, and FRAP assays [ 90 ].…”
Section: Antioxidant Activity Of Selected Prominent Foodsmentioning
confidence: 99%
“…The antioxidant capacity of methanol extracts from both tomato cultivars was performed using our previously reported method. 28 2,4,6-Tris(2 pyridyl)-triazine (TPTZ) (10 mM in 40 mM HCl), sodium acetate buffer (300 mM, pH 3.6), and ferric chloride hexahydrate (20 mM) in a ratio of 1:10:1 (v/v/v) were mixed to prepare FRAP working solution. An aliquot of tomato extracts (20 μL) with a concentration of 20 mg/mL was added to a 96-well plate.…”
Section: ■ Introductionmentioning
confidence: 99%